Meta-analysis of effect of vegetarian diet on ischemic heart disease and all-cause mortality - Ahmad Jabri; Ashish Kumar; Elizabeth Verghese; Anas Alameh; Anirudh Kumar; Muhammad Shahzeb Khan; Safi U. Khan; Erin D. Michos; Samir R. Kapadia; Grant W. Reed; Ankur Kalra (Elsevier, 2021)
Objective: To summarize the association between vegetarian versus non-vegetarian diet on mortality due to ischemic heart disease, cerebrovascular disease, or all-cause mortality. Methods: We searched PubMed, Cochrane databases, and ClinicalTrials.Gov from the inception of the databases to October 2019 with no language restriction. Randomized controlled trials or prospective observational studies comparing the association between vegetarian versus non-vegetarian diets among adults and reporting major adverse cardiovascular outcomes were selected. We used Paule-Mandel estimator for tau2 with Hartung-Knapp adjustment for random effects model to estimate risk ratio [RR] with 95% confidence interval [CI].The primary outcome of interest was all-cause mortality. The secondary outcome was ischemic heart disease mortality. Results: Eight observational studies (n = 131,869) were included in the analysis. Over a weighted mean follow-up of 10.68 years, very low certainty of evidence concluded that a vegetarian diet compared with a non-vegetarian diet was associated with similar risk of all-cause (RR: 0.84, 95% CI: 0.65-1.07, I2: 97%) or cerebrovascular mortality (RR: 0.84, 95% CI: 0.63-1.14, I2: 90%), but was associated with a reduced risk of ischemic heart disease mortality (RR: 0.70, 95% CI: 0.55-0.89, I2: 82%). Conclusion: A vegetarian diet, compared with a non-vegetarian diet, was associated with a reduced risk of ischemic heart disease mortality, whereas it had no effect on all-cause and cerebrovascular mortality. However, the results are to be considered with caution considering the low certainty of evidence. Despite recent studies supporting no restriction on animal protein intake gaining wide media attention and public traction, consideration for vegetarianism amongst those with risk factors for coronary artery disease should be contemplated.